PERAN GURU DALAM MEMBANGUN REPUTASI SEKOLAH MELALUI KOMUNIKASI ORGANISASI - Sinta Paramita; Riris Loisa; Yugih Setyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Problems related to organizational communication climate are still a severe problem in Indonesia. Cases related to conflict problems in various organizations occur at multiple levels, ranging from small organizations or institutions to rice, including educational institutions. By creating an atmosphere of an excellent organizational communication climate, educational services such as learning, and others can make the school's image and reputation. Therefore, the Fikom Untar PKM Team strives to help schools build a good reputation in organizational communication. The theme raised by the Fikom Untar PKM Team was